The Effect of Public Accountability, Employee Performance, Supervision, and Legislation on the Quality of Financial Reports in Preventing Fraud (A Study of the West Papua Provincial BPKAD Office) - Sudarwadi, Hustianto; Ijo, Evaristus Yohanes Andry Jaya; Sumari, Jenita; Sudarwadi, Dirarini (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the effect of public accountability, employee performance, supervision, and legislation on the quality of financial reports in preventing fraud at the Regional Financial and Asset Management Agency (BPKAD) of West Papua Province. This study uses a quantitative approach with a questionnaire survey of BPKAD employees. The data were analyzed using multiple linear regression preceded by validity, reliability, and classical assumption tests to ensure the model's feasibility. The results show that public accountability and employee performance do not significantly affect the quality of financial statements in the context of fraud prevention. Conversely, supervision and compliance with laws and regulations have a significant and positive effect on the quality of financial statements. Simultaneously, these four variables contribute to the production of more reliable financial reports, thereby enhancing fraud prevention. These findings emphasize the importance of strengthening the functions of supervision and regulatory compliance in regional financial management, accompanied by capacity-building for officials and the reinforcement of a culture of integrity, so that financial reports not only meet formal compliance requirements but also reflect integrity. However, they are also effective tools for public accountability and fraud prevention.